2015
DOI: 10.7717/peerj.790
|View full text |Cite
|
Sign up to set email alerts
|

Availability of mobile phones for discharge follow-up of pediatric Emergency Department patients in western Kenya

Abstract: Objective. Mobile phones have been successfully used for Emergency Department (ED) patient follow-up in developed countries. Mobile phones are widely available in developing countries and may offer a similar potential for follow-up and continued care of ED patients in low and middle-income countries. The goal of this study was to determine the percentage of families with mobile phones presenting to a pediatric ED in western Kenya and rate of response to a follow-up phone call after discharge.Methods. A prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, obtaining long-term follow-up of patients is challenging for STSMs-and there are few descriptions of the methods used to achieve such follow-up and even fewer reports of clinical outcomes-making determination of their success challenging [3,6]. Achieving patient follow-up is challenging even for established hospital systems in rural, resource-poor settings where STSMs often function, but there is evidence that mobile phones may enhance patient follow-up in such settings, including rural Haiti [7][8][9][10][11][12]. The aim of this study was two-fold: 1) to evaluate the efficacy of mobile phones to facilitate long-term patient follow-up (> one year) among a cohort of STSM patients in rural Haiti and 2) to measure longterm surgical outcomes, particularly late postoperative complications (POC) and the impact of operations upon patient quality of life (QOL), not measurable in the perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…However, obtaining long-term follow-up of patients is challenging for STSMs-and there are few descriptions of the methods used to achieve such follow-up and even fewer reports of clinical outcomes-making determination of their success challenging [3,6]. Achieving patient follow-up is challenging even for established hospital systems in rural, resource-poor settings where STSMs often function, but there is evidence that mobile phones may enhance patient follow-up in such settings, including rural Haiti [7][8][9][10][11][12]. The aim of this study was two-fold: 1) to evaluate the efficacy of mobile phones to facilitate long-term patient follow-up (> one year) among a cohort of STSM patients in rural Haiti and 2) to measure longterm surgical outcomes, particularly late postoperative complications (POC) and the impact of operations upon patient quality of life (QOL), not measurable in the perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Reported access to a mobile phone was considerably less than the 89.3% cited for patients in urban areas in low-and middle-income countries (LMICs). 5 This difference may be attributable to lower affluence, poorer accessibility to mobile phones and network coverage in rural areas.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in Kenya have reported a two-fold increase in adherence for anti-retroviral treatment with text message (SMS) reminders. Likewise caregivers of paediatric patients attending emergency department had an 83.6% follow-up rates when reminded by SMS [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%